Does educational intervention affect resident competence in sonographic cervical length measurement?. (2nd August 2016) - Vahanian, Sevan A.; Gallagher, Kathryn; Chavez, Martin R.; Kinzler, Wendy L.; Vintzileos, Anthony M.
Abstract: Objective : To determine if a structured teaching module improves resident competency in transvaginal sonographic cervical length measurements. Methods : This was a prospective cohort study involving obstetrics and gynecology residents at a single institution. Residents collected 10 transvaginal cervical images from patients with threatened preterm labor presenting to Labor and Delivery. After initial image acquisition, residents participated in a lecture-based teaching module involving a pre- and post-intervention assessment. Following the didactic session, they collected 10 additional images. All the images were scored independently by two Maternal–Fetal Medicine attending physicians based on the quality and accuracy of the measured cervical length. Pre-and post- intervention test results were compared, as well as pre- and post- intervention image scores. Parametric and nonparametric tests were used as appropriate with p  < 0.05 considered significant. Results : Ninety-three percent of the residents (14/15) improved their scores from pre-test to post-test or maintained an already perfect score ( p  < 0.01). Improvement was most significant with the junior residents. Seventy-nine percent of the residents (11/14) improved their cervical image scores after the educational session. Mean score for total residents was 73.7 + 12.6 pre-intervention and 90.2 + 9.9 post-intervention ( p  < 0.01) out of a total of 120. Conclusions : There is an improvement in the competence of resident measured cervical lengths via transvaginal ultrasound when a structured educational module is implemented for resident education.